Diagnostic Accuracy of Multidetector Computed Tomography (MDCT) in Evaluation of Varices in Cirrhotic Patients (Medical Forum Monthly, 2024)
Objective: To evaluate the diagnostic accuracy of Multidetector Computed Tomography in detection of esophageal varices in cirrhotic patients comparing with Upper GI endoscopy results.Study Design: Observational study.Place and Duration of Study: This study was conducted at the Department of Nishtar Medical Teaching Hospital from Oct, 2016 to Oct, 2017.Materials and Methods: Total 172 patients with liver cirrhosis and portal hypertension (Portal vein diameter > 13mm) on ultrasound were included in the study. After unenhanced scanning, helical images were obtained during the hepatic arterial and portovenous phase. Negative oral contrast was given to all patients 30 to 45 minutes before examination. Endoscopic diagnosis of esophageal varices was obtained from medical record of the patients. Using SPSS-18, data was analyzed and diagnostic accuracy, positive predictive value, negative predictive value, sensitivity and specificity were calculated.Results: 172 patients were included in study according to inclusion criteria. Patients mean age was 45.01±6.48 years with range of 25(35-60) years. Male patients were 55.81 % (n=96), and 44.18% (n=76) were female. The overall mean duration of disease was 43.82±12.55 months, with range of 45(19-64) months. MDCT scan was true positive for 126 and true negative for 23 patients. False negative were 23 and false positive only 3 patients. Diagnostic accuracy, positive predictive value (PPV), negative predictive value (NPV), sensitivity and specificity of MDCT were 84.88%,97.61%, 50.00 %, 84.24%, and 84.46% respectively.Conclusion: MDCT is a new non-invasive diagnostic modality with significantly high accuracy in diagnosis of varices in cirrhotic patients with portal hypertension that are comparable with upper GI endoscopy.